2018
DOI: 10.1021/acs.jpclett.8b02757
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Signature of Oxidized Oxygen States in Peroxides

Abstract: Recent debates on the oxygen redox behaviors in battery electrodes have triggered a pressing demand for the reliable detection and understanding of non-divalent oxygen states beyond conventional absorption spectroscopy. Here, enabled by high-efficiency mapping of resonant inelastic X-ray scattering (mRIXS) coupled with first-principles calculations, we report distinct mRIXS features of the oxygen states in Li2O, Li2CO3, and especially, Li2O2, which are successfully reproduced and interpreted theoretically. mRI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 39 publications
(139 reference statements)
6
116
0
Order By: Relevance
“…The O K ‐edge spectrum of Li 2 RuO 3 in the TEY and TFY modes at various charge/discharge states are shown in Figure S10 in the Supporting Information. No sign of the oxygen redox is observed in the surface‐sensitive TEY mode or the bulk‐sensitive TFY mode (A peak expected to appear at ≈530.8 eV as the fingerprint of the O redox . This characteristic peak of O (2− σ )− is also confirmed by the our differential spectra between 4.00 V (below the plateau) and 4.60 V (fully charged state), as is exhibited in Figure S11 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 75%
“…The O K ‐edge spectrum of Li 2 RuO 3 in the TEY and TFY modes at various charge/discharge states are shown in Figure S10 in the Supporting Information. No sign of the oxygen redox is observed in the surface‐sensitive TEY mode or the bulk‐sensitive TFY mode (A peak expected to appear at ≈530.8 eV as the fingerprint of the O redox . This characteristic peak of O (2− σ )− is also confirmed by the our differential spectra between 4.00 V (below the plateau) and 4.60 V (fully charged state), as is exhibited in Figure S11 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 75%
“…Second, compared with the pristine state (Figure d), O ‐K mRIXS of the 4.8 V charged electrode shows enhanced intensity at 523.7 eV emission and 531 eV excitation energies (white arrow in Figure e). It has been established that an enhanced mRIXS feature here is a signature of partially occupied O ‐ 2p bands in non‐divalent oxygen, that is, oxidized oxygen, thus providing a reliable fingerprint of l‐OR states in charged electrodes . Indeed, Figure f shows the integrated mRIXS intensity around 531 eV excitation energy, which displays a gradual enhancement of the intensity at 523.7 eV (shaded range) during charging, indicating oxidized oxygen in the charged electrodes at high potentials.…”
Section: Methodsmentioning
confidence: 99%
“…[8] As shown in Figure 2b,c, partial Ni 2+ ions were oxidized to Ni 3+ and Ni 4+ ions upon charging up to 4.3 V, and during the subsequent charging process,t he oxidation states of the Ni ions remains relatively stable.F or the F À ,T i 4+ and Nb 5+ ions,t here is no observable evidence that they participate in the charge compensation ( Figure S6 Figure 2e). It has been established that an enhanced mRIXS feature here is as ignature of partially occupied O-2p bands in non-divalent oxygen, that is,o xidized oxygen, [10] thus providing ar eliable fingerprint of l-OR states in charged electrodes. [8a] Indeed, Figure 2f shows the integrated mRIXS intensity around 531 eV excitation energy,w hich displays ag radual enhancement of the intensity at 523.7 eV (shaded range) during charging,i ndicating oxidized oxygen in the charged electrodes at high potentials.N ote that well isolated l-OR mRIXS feature has been found in various charged electrodes including Li-rich layered oxides, [8a] but charged LTNNbOF displays only an enhanced shoulder feature here.This is mainly due to the overlapping of l-OR and Ti-O hybridization features at exactly the same excitation energy at 531 eV,leading to only ashoulder, instead of an isolated feature,ofthe l-OR signals in LTNNbOF.N onetheless,t he systematic evolution of the 523.7 eV shoulder in Figure 2fupon cycling reveals the l-OR reactions in LTNNbOF,a nd more importantly,t he intensity drops in the following discharging, indicating areversible l-OR activity.…”
mentioning
confidence: 99%
“…41 Similar spectroscopic features have been observed in lithium peroxide. 40,59 In contrast, simulated spectra of stretched peroxide molecules suggest that an O − species would not have an absorption feature near 531 eV. 30 Although it has been suggested that molecular oxygen or peroxide ions are forming reversibly during electrochemical cycling, 34,[43][44][45] such species could also be the product of the irreversible decomposition of the cathode.…”
Section: Critical Analysis Of Oxygen Redoxmentioning
confidence: 99%
“…39 Furthermore, the spectroscopic feature attributed to O − is consistent with molecular oxygen and peroxide ions. 31,[40][41][42] These considerations motivate a re-examination of possible redox mechanisms in the Li-excess Mn oxides.…”
Section: Introductionmentioning
confidence: 99%